THE BUILDING OPENS UP AN OFTEN OPAQUE AND PRIVATE AREA OF STUDY. - Powell, Kenneth (Architects' Journal, 2007)
The article focuses on the architectural design of Grimshaw's University College London (UCL) Cancer Institute in London, England. The plan of the building is highly repetitive on the first to fourth floors, providing a clear diagram for servicing the vertical stack of laboratories. Write-up areas are pushed out beyond the grid line of the structural steel frame using coffered precast-concrete slabs.